2017
DOI: 10.1063/1.5002743
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreflectance microscopy measurements of the Joule heating characteristics of high-Tc superconducting terahertz emitters

Abstract: Joule heating is the central issue in order to develop high-power and high-performance terahertz (THz) emission from mesa devices employing the intrinsic Josephson junctions in a layered high transition-temperature Tc superconductor. Here, we describe a convenient local thermal measurement technique using charge-coupled-device-based thermoreflectance microscopy, with the highest spatial resolution to date. This technique clearly proves that the relative temperature changes of the mesa devices between different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Since the out-of-plane resistivity of this material decreases with increasing temperature, the current-voltage characteristics (IVCs) exhibit a positive differential resistance at low currents but start to back-bend at larger currents and the differential resistance becomes negative. Above some current in the back-bending region, the current and temperature distribution in the stack become strongly nonuniform and a hot spot (i.e., a region with a temperature above T c ) forms [8,11,19,21,38,50,57]. The hot spot can coexist with regions that are still superconducting, producing terahertz radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the out-of-plane resistivity of this material decreases with increasing temperature, the current-voltage characteristics (IVCs) exhibit a positive differential resistance at low currents but start to back-bend at larger currents and the differential resistance becomes negative. Above some current in the back-bending region, the current and temperature distribution in the stack become strongly nonuniform and a hot spot (i.e., a region with a temperature above T c ) forms [8,11,19,21,38,50,57]. The hot spot can coexist with regions that are still superconducting, producing terahertz radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The local temperature distributions TðrÞ of the IJJ mesa devices have been measured in detail, and the results have been discussed in comparison with theoretical studies. [14][15][16][40][41][42][43][44][45]51,[63][64][65][66][78][79][80] These studies concluded that the spontaneous formation of a local temperature instability known as a hot spot can occur in the IJJ-THz emitter device due to both the quasi-two-dimensional thermal and electrical conductivities, the latter yielding a semiconducting-like temperature dependence of the c-axis normal state resistivity for under-doped Bi2212 single crystals. Previous studies revealed that a hot spot, within which the local temperature TðrÞ > T c , acts as a shunt resistance inserted parallel to the 0021-8979/2018/124(3)/033901/9/$30.00…”
Section: Introductionmentioning
confidence: 96%
“…However, a major issue affecting the reliability and the upper limit of the emission frequency has been the Joule heating of the mesas [20][21][22], especially when they have Bi2212 substrates, since Bi2212 is a very poor thermal conductor. But this problem has been mostly removed by fabricating stand-alone mesas, in which the Bi2212 sample is doubly cleaved to a thickness of 1-2 microns from a single crystal, and the top and bottom surfaces are each coated with a thin layer of gold [12][13][14][23][24][25][26][27]. These issues are discussed in Section VIII.…”
Section: Introductionmentioning
confidence: 99%